Material Properties of n‐Type β‐Ga2O3 Epilayers with In Situ Doping Grown on Sapphire by Metalorganic Chemical Vapor Deposition - Fu‐Gow Tarntair; Chih‐Yang Huang; Siddharth Rana; Kun‐Lin Lin; Shao‐Hui Hsu; Yu‐Cheng Kao; Singh Jitendra Pratap; Yi‐Che Chen; Niall Tumilty; Po‐Liang Liu; Ray‐Hua Horng (Advanced Electronic Materials)
Abstract In this study, in situ, Si‐doped heteroepitaxial Ga2O3 layers are grown on c‐plane sapphire by metalorganic chemical vapor deposition. The X‐ray diffraction peaks of the doped Ga2O3 epilayers shows ß‐phase of Ga2O3 ,and full width at half maximum of Ga2O3 crystallinity is decreased at a Tetraethoxysilane (TEOS) molar flow rate of 2.23 × 10−7 mol min−1 but increased with higher flow rates. The dopant concentrations of Ga2O3 grown at 825 °C with TEOS molar flows of 2.23 × 10−7, 4.47 × 10−7, and 6.69 × 10−7 mol min−1 are measured to be 5.5 × 1019, 1.1 × 1020, and 1.4 × 1020 atom cm−3, respectively, using secondary ion mass spectra and Hall measurements reveal n‐type nature with carrier concentrations of 6.5 × 1017, 3.2 × 1018, and 3.9 × 1018 atom/cm3 , respectively. To increase Si dopant activation, Ga2O3 growth temperature is raised to 875 °C. The result suggests a higher growth temperature can contribute to a greater probability of Si substitution on Ga lattice sites, which further reduces the resistivity of Ga2O3 epilayer. Moreover, results are compared with theoretical Density Functional Theory  studies.